1976
DOI: 10.1111/j.1348-0421.1976.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies of Specificity of Antibodies Contained in Antiserum against Poliovirus

Abstract: Antigenic components of Mahoney strain (poliovirus type 1) involved in virus neutralization reaction were analyzed with mutant Mahoney strains resistant to inhibitors in equine serum (inhibitorresistant mutants) by means of the kinetic neutralization test. It was shown that absorption of antiMahoney serum with five inhibitor-resistant mutants yielded sera with different antibodies, of which three had distinct specificities and two specificities possibly partly related to one of those three sera. Further, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Absorption of antiMahoney serum with these inhibitor-resistant Mahoney strains yielded five antibodies with different specificities in neutralization reaction (designated as HN31, HN11, H33, HS77, and H520 antibodies) (14). A detailed experiment carried out subsequently (15), however, showed that while three (HN31, HN11, and H33 antibodies) of those five antibodies had mutually distinct specificities, the remaining two had specificities partly related to one of the three (H33 antibody). These results indicate that poliovirus-neutralizing antibody consists of several kinds of antibody having different specificities, and therefore it might be that the surface of the virus particle carries multiple distinct antigenic determinants.…”
mentioning
confidence: 99%
“…Absorption of antiMahoney serum with these inhibitor-resistant Mahoney strains yielded five antibodies with different specificities in neutralization reaction (designated as HN31, HN11, H33, HS77, and H520 antibodies) (14). A detailed experiment carried out subsequently (15), however, showed that while three (HN31, HN11, and H33 antibodies) of those five antibodies had mutually distinct specificities, the remaining two had specificities partly related to one of the three (H33 antibody). These results indicate that poliovirus-neutralizing antibody consists of several kinds of antibody having different specificities, and therefore it might be that the surface of the virus particle carries multiple distinct antigenic determinants.…”
mentioning
confidence: 99%
“…The method of plaque assay was described elsewhere (17). Briefly, MS cell monolayers in 70 mm petri dishes were inoculated with 0.4 ml of virus, covered with 8 ml of first overlay medium, and then kept at 37 C for 2 days in a CO2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Further, by absorbing anti-Mahoney serum with these mutants, we isolated five kinds of antibodies with different specificities among which, in subsequent experiments (17), three were shown to have distinct specificities and also two specificities partly related to one of the three. This result shows that the an ti-Mahoney serum contains at least three different antibodies having distinct specificities, possibly indicating the presence of at least three different antigenic determinant sites on the virus surface.…”
mentioning
confidence: 99%
“…Urasawa et al (19,20) reported that they succeeded in obtaining various serological variants of poliovirus type 1, Mahoney, using virus inhibitory substances in equine sera and each variant showed resistance to one of several mono-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%